PARADIGM UNIFORMITY AND ANALOGY: THE CAPITALISTIC VERSUS MILITARISTIC DEBATE - David Eddington (International Journal of English Studies (IJES), 2006)
In American English, /t/ in capitalistic is generally flapped while in militaristic it is not due to the influence of capi[ɾ]al and mili[tʰ]ary. This is called Paradigm Uniformity or PU (Steriade, 2000). Riehl (2003) presents evidence to refute PU which when reanalyzed supports PU.
PU is thought to work in tandem with a rule of allophonic distribution, the nature of which is debated. An approach is suggested that eliminates the need for the rule versus PU dichotomy; allophonic distribution is carried out by analogy to stored items in the mental lexicon. Therefore, the influence of the pronunciation of capital on capitalistic is determined in the same way as the pronunciation of /t/ in monomorphemic words such as Mediterranean is. A number of analogical computer simulations provide evidence to support this notion.